Evolução da linha de costa nos deltas do nordeste brasileiro - Ferreira, Thiago Augusto Bezerra (2024)
Deltas, serving as significant hubs for agriculture, industry, and energy, are susceptible to coastal erosion owing to anthropogenic pressures in both the drainage basins and the coastal zone. This study investigates alterations in the shoreline of three Northeastern Brazilian deltas (São Francisco, Parnaíba, and Jequitinhonha) from the 1980s to 2021, correlating them with both human-induced and natural impacts. Multispectral imagery was utilized to assess horizontal changes in the shoreline through the DSAS software, providing insights into long-term trends across different decades. Additionally, variations in the active coastal area were analyzed for the same periods. Furthermore, for the São Francisco delta, sandbanks downstream of the Xingó dam were delineated using satellite imagery. Hydro-climatic data from stations proximate to the coastal zone were also incorporated into the study. The data reveals that the Parnaíba Delta demonstrated a progradation rate at its mouth surpassing 20 m/year, resulting in sedimentary gains of 6 km² across the delta. In contrast, the Jequitinhonha delta experienced predominant erosion processes at the mouth, characterized by rates below 10 m/year and an increased delta mouth protrusion angle of 13° from 1984 to 2021. The limited correlation of the active coastal area (R² = 0.49) suggests that sediments eroded at the mouth are transported, via bidirectional currents, to the delta's margins. Among the three deltas, the São Francisco delta exhibited pronounced erosion at the mouth, with losses exceeding 20 m/year, reaching up to 50 m/year. The angle of the mouth increased by 18° during the analyzed period, and there was a net loss of 6.2 km². Due to sparse human habitation along the coast, the construction of dams within approximately 100 km of the coastal zone has emerged as a significant contributing factor to erosion processes in the Jequitinhonha and São Francisco deltas. Prior to the construction of the Itapebi and Xingó dams, both deltas exhibited relative stability in their coastlines. However, post-dam construction, Net Shoreline Movement (NSM) data indicated a gradual increase in erosion at the mouths over time. Additionally, these structures reduced the annual and monthly variability of the lower river courses of the Jequitinhonha and São Francisco, resulting in a diminished capacity for riverbank erosion and sediment transport to the coastal area. For instance, within the São Francisco delta, spanning from 1984 to 2021, there was a reduction of 7.54 km² in the sandy banks downstream of the Xingó dam. This figure exceeds threefold the loss of active coastal area observed across the entirety of the delta. Notably, this phenomenon did not occur in the Parnaíba delta, as the Boa Esperança dam is situated 600 km away from the coastal zone. Climate change, alongside potential mining and dredging activities, may further alter the stability of the Parnaíba Delta and exacerbate erosion processes in the Jequitinhonha and São Francisco Deltas. Over the last two decades, northeastern Brazil has experienced a reduction of more than 30% in rainfall. IPCC data suggests a projected 60 to 70% reduction in rainfall in this region by 2100. Consequently, the capacity for river transport is expected to decrease significantly, thereby intensifying erosion processes in both deltas.